Impacts of Fair Trade-Certified Coffee in Nicaragua,Brazil, Honduras, and Peru: Implications for livelihoods and empowerment of farm workers and independent smallholder producers. - Río Duque, Martha Lilia del; González, Carolina; Córdoba, Diana M.; Howland, Fanny C.; Gutiérrez, Natalia; Lundy, Mark M. (International Center for Tropical Agriculture, 2017)
Context: